Historiográfia a szintézisíráshoz 4.: Rákosi Mátyás 1945 utáni politikai pályafutásával kapcsolatos könyvek - Gulyás, László (Közép-Európai Közlemények, 2024)
Mátyás Rákosi was already a member of the narrow circle of most important politicians between 1945 and 1948. But his name primaraly symbolizes the period between 1948 and 1956. That is why we call dictatorship. In the present historiographical study the writings related three broad catagories: 1. books about him 2. His memoir 3. his species, articled, books.